Environmental exposure does not explain putative maladaptation in road-adjacent populations. - Brady, Steven P (Oecologia, 2017)
While the ecological consequences of roads are well described, little is known of their role as agents of natural selection, which can shape adaptive and maladaptive responses in populations influenced by roads. This knowledge gap persists despite a growing appreciation for the influence of evolution in human-altered environments. There, insights indicate that natural selection typically results in local adaptation. Thus, populations influenced by road-induced selection should evolve fitness advantages in their local environment. Contrary to this expectation, wood frog tadpoles from roadside populations show evidence of a fitness disadvantage, consistent with local maladaptation. Specifically, in reciprocal transplants, roadside populations survive at lower rates compared to populations away from roads. A key question remaining is whether roadside environmental conditions experienced by early stage embryos induce this outcome. This represents an important missing piece in evaluating the evolutionary nature of this maladaptation pattern. Here, I address this gap using a reciprocal transplant experiment designed to test the hypothesis that embryonic exposure to roadside pond water induces a survival disadvantage. Contrary to this hypothesis, my results show that reduced survival persists when embryonic exposure is controlled. This outcome indicates that the survival disadvantage is parentally mediated, either genetically and/or through inherited environmental effects. This result suggests that roadside populations are either truly maladapted or potentially locally adapted at later life stages. I discuss these interpretations, noting that regardless of mechanism, patterns consistent with maladaptation have important implications for conservation. In light of the pervasiveness of roads, further resolution explaining maladaptive responses remains a critical challenge in conservation.
Keywords: *Adaptation, Physiological; *Environmental Exposure; *Ranidae; *Selection, Genetic; Acclimatization; Adaptation, Physiological; Amphibia; Amphibians; Animals; Contemporary evolution; Environmental Exposure; Inherited environmental effects; Larva; Local adaptation; Rana sylvatica; Ranidae; Ranidae/ph [Physiology]; Runoff; Selection, Genetic; acclimatization; adaptation; amphibian; animal; dept.bio; embryonic development; environmental conditions; environmental effect; environmental exposure; evolutionary biology; fitness; frog; genetic selection; larva; local adaptation; natural selection; physiology; pond; population type; roadside environment; runoff; survival

Positive sire effects and adaptive genotype by environment interaction occur despite pattern of local maladaptation in roadside populations of an amphibian - Brady, Steven P.; Goedert, Debora (Copeia, 2017)
The global road network causes many negative ecological effects. Contrasting our knowledge of these effects, insights into evolutionary consequences of roads remain undeveloped. Here, we study a suite of populations of the Wood Frog that appear to be evolving maladaptively in response to road-adjacency. Specifically, when raised together in roadside pools, roadside populations survive at lower rates compared to populations away from roads. To begin to understand the cause of this survival disadvantage, we investigated potential parental and genetic sources of maladaptation. First, to assess whether parental effects might induce maladaptation, we measured adult body weight to length ratio ('relative weight') and its influence on offspring survival in a reciprocal transplant experiment across 12 populations. Next, to assess whether genetic effects might limit adaptive responses in offspring, we estimated genetic correlations between environments for survival and fitness-related traits. We found that relative weight was higher in roadside populations and, for males, had a positive influence on offspring survival. This demonstrates a novel transgenerational effect of Wood Frog adult males but suggests that this effect is not causing maladaptive survival. Genetic correlations indicated that a subset of roadside genotypes respond adaptively to road-adjacency despite population level maladaptive survival. This suggests that metapopulation dynamics and/or high levels of nonadditive genetic variance may be limiting adaptation or that insufficient time has elapsed for adaptation to occur. Together, these results highlight the complexity and scale of responses to a pervasive feature of landscape alteration revealed by evolutionary approaches.
Keywords: Amphibia; Rana sylvatica; adaptation; amphibian; dept.bio; environmental conditions; evolutionary biology; frog; genotype; genotype-environment interaction; heritability; local adaptation; metapopulation; population type; roadside environment; survival

Road ecology: shifting gears toward evolutionary perspectives - Brady, Steven P.; Richardson, Jonathan L. (Frontiers in Ecology and the Environment, 2017)
Recent advances in understanding the often rapid pace of evolution are reshaping our view of organisms and their capacity to cope with environmental change. Though evolutionary perspectives have gained traction in many fields of conservation, road ecology is not among them. This is surprising because roads are pervasive landscape features that generate intense natural selection. The biological outcomes from these selection pressures – whether adaptive or maladaptive – can have profound consequences for population persistence. We argue that studying evolutionary responses is critical to accurately understand the impacts of roads. Toward that end, we describe the basic tenets and relevance of contemporary evolution and showcase the few examples where it has been documented in road ecology. We outline practical ways that road ecologists can estimate and interpret evolutionary responses in their research. Finally, we suggest priority research topics and discuss how evolutionary insights can inform conservation in landscapes traversed by roads.
Keywords: dept.bio; peer-reviewed

Incorporating evolutionary insights to improve ecotoxicology for freshwater species - Brady, Steven P.; Richardson, Jonathan L.; Kunz, Bethany K. (Evolutionary Applications, 2017)
Ecotoxicological studies have provided extensive insights into the lethal and sublethal effects of environmental contaminants. These insights are critical for environmental regulatory frameworks, which rely on knowledge of toxicity for developing policies to manage contaminants. While varied approaches have been applied to ecotoxicological questions, perspectives related to the evolutionary history of focal species or populations have received little consideration. Here, we evaluate chloride toxicity from the perspectives of both macroevolution and contemporary evolution. First, by mapping chloride toxicity values derived from the literature onto a phylogeny of macroinvertebrates, fish, and amphibians, we tested whether macroevolutionary relationships across species and taxa are predictive of chloride tolerance. Next, we conducted chloride exposure tests for two amphibian species to assess whether potential contemporary evolutionary change associated with environmental chloride contamination influences chloride tolerance across local populations. We show that explicitly evaluating both macroevolution and contemporary evolution can provide important and even qualitatively different insights from those obtained via traditional ecotoxicological studies. While macroevolutionary perspectives can help forecast toxicological end points for species with untested sensitivities, contemporary evolutionary perspectives demonstrate the need to consider the environmental context of exposed populations when measuring toxicity. Accounting for divergence among populations of interest can provide more accurate and relevant information related to the sensitivity of populations that may be evolving in response to selection from contaminant exposure. Our data show that approaches accounting for and specifically examining variation among natural populations should become standard practice in ecotoxicology.
Keywords: LC50; acute exposure; adaptation; chloride; dept.bio; maladaptation; peer-reviewed; road salt runoff

Fundamental and applied pursuits in evolutionary toxicology are mutually beneficial: A reply to Hahn (2018). - Brady, Steven P; Monosson, Emily; Matson, Cole; Bickham, John W (Evolutionary applications, 2019)
Keywords: Evolutionary toxicology; contemporary evolution; dept.bio; ecotoxicology; peer-reviewed

Evolutionary toxicology: Toward a unified understanding of life's response to toxic chemicals. - Brady, Steven P; Monosson, Emily; Matson, Cole W; Bickham, John W (Evolutionary Applications, 2017)
Keywords: dept.bio; peer-reviewed

Physiological consequences of exposure to salinized roadside ponds on wood frog larvae and adults - Hall, Emily M.; Brady, Steven P.; Mattheus, Nichole M.; Earley, Ryan L.; Diamond, Molly; Crespi, Erica J. (Biological Conservation, 2017)
Keywords: dept.bio

Fitter frogs from polluted ponds: The complex impacts of human-altered environments - Brady, Steven P.; Zamora‐Camacho, Francisco J.; Eriksson, Fredrik A. A.; Goedert, Debora; Comas, Mar; Calsbeek, Ryan (Evolutionary Applications, 2019)
Human-modified habitats rarely yield outcomes that are aligned with conservation ideals. Landscapes that are subdivided by roads are no exception, precipitating negative impacts on populations due to fragmentation, pollution, and road kill. Although many populations in human-modified habitats show evidence for local adaptation, rarely does environmental change yield outright benefits for populations of conservation interest. Contrary to expectations, we report surprising benefits experienced by amphibian populations breeding and dwelling in proximity to roads. We show that roadside populations of the wood frog, Rana sylvatica, exhibit better locomotor performance and higher measures of traits related to fitness compared with frogs from less disturbed environments located further away from roads. These results contrast previous evidence for maladaptation in roadside populations of wood frogs studied elsewhere. Our results indicate that altered habitats might not be unequivocally detrimental and at times might contribute to metapopulation success. While the frequency of such beneficial outcomes remains unknown, their occurrence underscores the complexity of inferring consequences of environmental change.
Keywords: amphibian; dept.bio; human-modified habitats; maladaptation; peer-reviewed; road salt; roads

Conservation through the lens of (mal)adaptation: Concepts and meta-analysis - Derry, Alison Margaret; Fraser, Dylan J.; Brady, Steven P.; Astorg, Louis; Lawrence, Elizabeth R.; Martin, Gillian K.; Matte, Jean-Michel; Dastis, Jorge Octavio Negrín; Paccard, Antoine; Barrett, Rowan D. H.; Chapman, Lauren J.; Lane, Jeffrey E.; et al. (Evolutionary Applications, 2019)
Evolutionary approaches are gaining popularity in conservation science, with diverse strategies applied in efforts to support adaptive population outcomes. Yet conservation strategies differ in the type of adaptive outcomes they promote as conservation goals. For instance, strategies based on genetic or demographic rescue implicitly target adaptive population states whereas strategies utilizing transgenerational plasticity or evolutionary rescue implicitly target adaptive processes. These two goals are somewhat polar: adaptive state strategies optimize current population fitness, which should reduce phenotypic and/or genetic variance, reducing adaptability in changing or uncertain environments; adaptive process strategies increase genetic variance, causing maladaptation in the short term, but increase adaptability over the long term. Maladaptation refers to suboptimal population fitness, adaptation refers to optimal population fitness, and (mal)adaptation refers to the continuum of fitness variation from maladaptation to adaptation. Here, we present a conceptual classification for conservation that implicitly considers (mal)adaptation in the short-term and long-term outcomes of conservation strategies. We describe cases of how (mal)adaptation is implicated in traditional conservation strategies, as well as strategies that have potential as a conservation tool but are relatively underutilized. We use a meta-analysis of a small number of available studies to evaluate whether the different conservation strategies employed are better suited toward increasing population fitness across multiple generations. We found weakly increasing adaptation over time for transgenerational plasticity, genetic rescue, and evolutionary rescue. Demographic rescue was generally maladaptive, both immediately after conservation intervention and after several generations. Interspecific hybridization was adaptive only in the F1 generation, but then rapidly leads to maladaptation. Management decisions that are made to support the process of adaptation must adequately account for (mal)adaptation as a potential outcome and even as a tool to bolster adaptive capacity to changing conditions.
Keywords: adaptation; demographic rescue; dept.bio; evolutionary rescue; gene flow; genetic rescue; hybridization; peer-reviewed; transgenerational plasticity; translocation

Causes of maladaptation. - Brady, Steven P; Bolnick, Daniel I; Angert, Amy L; Gonzalez, Andrew; Barrett, Rowan D H; Crispo, Erika; Derry, Alison M; Eckert, Christopher G; Fraser, Dylan J; Fussmann, Gregor F; Guichard, Frederic; Lamy, Thomas; et al. (Evolutionary applications, 2019)
Evolutionary biologists tend to approach the study of the natural world within a framework of adaptation, inspired perhaps by the power of natural selection to produce fitness advantages that drive population persistence and biological diversity. In contrast, evolution has rarely been studied through the lens of adaptation's complement, maladaptation. This contrast is surprising because maladaptation is a prevalent feature of evolution: population trait values are rarely distributed optimally; local populations often have lower fitness than imported ones; populations decline; and local and global extinctions are common. Yet we lack a general framework for understanding maladaptation; for instance in terms of distribution, severity, and dynamics. Similar uncertainties apply to the causes of maladaptation. We suggest that incorporating maladaptation-based perspectives into evolutionary biology would facilitate better understanding of the natural world. Approaches within a maladaptation framework might be especially profitable in applied evolution contexts - where reductions in fitness are common. Toward advancing a more balanced study of evolution, here we present a conceptual framework describing causes of maladaptation. As the introductory article for a Special Feature on maladaptation, we also summarize the studies in this Issue, highlighting the causes of maladaptation in each study. We hope that our framework and the papers in this Special Issue will help catalyze the study of maladaptation in applied evolution, supporting greater understanding of evolutionary dynamics in our rapidly changing world.
Keywords: adaptation; dept.bio; fitness; global change; maladaptation; peer-reviewed

Understanding maladaptation by uniting ecological and evolutionary perspectives - Brady, Steven P.; Bolnick, Daniel I.; Barrett, Rowan D. H.; Chapman, Lauren; Crispo, Erika; Derry, Alison M.; Eckert, Christopher G.; Fraser, Dylan J.; Fussmann, Gregor F.; Gonzalez, Andrew; Guichard, Frederic; Lamy, Thomas; et al. (The American Naturalist, 2019)
Evolutionary biologists have long trained their sights on adaptation, focusing on the power of natural selection to produce relative fitness advantages while often ignoring changes in absolute fitness. Ecologists generally have taken a different tack, focusing on changes in abundance and ranges that reflect absolute fitness while often ignoring relative fitness. Uniting these perspectives, we articulate various causes of relative and absolute maladaptation and review numerous examples of their occurrence. This review indicates that maladaptation is reasonably common from both perspectives, yet often in contrasting ways. That is, maladaptation can appear strong from a relative fitness perspective, yet populations can be growing in abundance. Conversely, resident individuals can appear locally adapted (relative to nonresident individuals) yet be declining in abundance. Understanding and interpreting these disconnects between relative and absolute maladaptation, as well as the cases of agreement, is increasingly critical in the face of accelerating human-mediated environmental change. We therefore present a framework for studying maladaptation, focusing in particular on the relationship between absolute and relative fitness, thereby drawing together evolutionary and ecological perspectives. The unification of these ecological and evolutionary perspectives has the potential to bring together previously disjunct research areas while addressing key conceptual issues and specific practical problems. © 2019 by The University of Chicago. All rights reserved.
Keywords: Adaptation; Fitness; Global change; Maladaptation; adult; article; dept.bio; drawing; ecologist; environmental change; female; global change; human; human experiment; male; natural selection; peer-reviewed; resident